Об условиях колеблемости и неколеблемости решений одного полулинейного дифференциального уравнения второго порядка - Евтухов, В.М. (Український математичний журнал, 1994)
We give sufficient conditions for oscillation and nonoscillation of regular solutions of some second-order differential equation.